Diseño y estudio de un sistema autónomo de seguridad utilizando paneles fotovoltaicos para sectores sin servicio eléctrico. - Cisneros Flores, Israel Alejandro (2019)
Due to high crime rate and electrical interconnection lacking in several areas of the country, it has been decided to design an autonomous system of an off-grid surveillance system powered by solar energy, thus using clean energy with a low level of pollution. In this thesis, we will cover renewable energies which will be carried out and we will analyze the necessary components to install an off-grid photovoltaic system. A brief study will be made of the security systems, covering the largest possible area, the total loads will also be analyzed in order to determine the appropriate devices so that they can feed the system in an optimal way. The operation and installation of the wireless data transmitters will be explained, and an electrical diagram will be created for an easy implementation of the project.